Catatonia in a psychiatric setup having diverse etiology: A case series - Raj Yalgi; Shubhangi Dere; Aakash Ponda; Darpan Kaur; Rakesh Ghildiyal (Industrial Psychiatry Journal)
Catatonia is a neuropsychiatric syndrome characterized by stupor, mutism, negativism, posturing, mannerisms, stereotypies, waxy flexibility, catalepsy, grimacing, echolalia, and echopraxia. This syndrome has a plethora of etiologies that arise from neurological and medical conditions, psychiatric illnesses, and withdrawal of psychoactive substances. Adding to this, it has numerous differentials, including an acute confusional state, which often adds to the diagnostic dilemma. The incidence of catatonia is between 5 and 20%. A comprehensive workup of the patient is required to rule out organic causes, after which a diagnosis of catatonia can be looked into for treatment. We present three case reports who presented with catatonic syndrome but had different etiologies.